PERILAKU CHAOS ALIRAN FLUIDA BERDENYUT DALAM SALURAN BERPENAMPANG SEGIEMPAT - Prayitno Ciptoadi; Mesak F. Noya; Gertruida S. Norimarna (ALE Proceeding, 2021)
The pulsatile fluid flow in a transverse grooved channel would become chaotic flows in low Reynold numbers. The Reynold number where flows become chaos depends on grooves distances. The objective of this research is to analyze the effect of grooves distances on the behavior of chaos. This research was done by implementing a closed square cross-section channel, where the bottom surface of the channel was semicircle grooved. The frequency of flow oscillation measurement was done by setting up a resistance sensor that is Wheatstone bridge where the resistance sensor was located in a U manometer. Measurement was done at several Reynold number. From the research result, it is seen that the periodic fluid flows in the transverse grooved channel had become chaos at Reynold number Re 950 in the channel without grooved and at Reynold number Re 700 in the grooved channel. Chaos took placed since a vortex appeared at every treatment.